Pelatihan Caregiver Keluarga dalam Merawat Lansia dengan Penyakit Degeneratif - Shinta Dwi Kurnia; Arina Lis Sa'adah; Yunita Rusidah; Anisa Sholikhati; Nindy Tanaya; Navira Septiana Ulfa (Jurnal Medika: Medika, 2026)
The decline in physiological functions in the elderly due to the aging process can be accompanied by degenerative diseases that can limit the independence of the elderly in activities of daily living (ADL). The task of families who act as primary caregiver s is very crucial, but is often hampered by limited knowledge and technical skills. This community service activity aims to improve the knowledge and skills of family caregiver s in caring for the elderly with degenerative diseases independently at home. The location of this community service was carried out in Singocandi Village, Kudus Regency on April 20, 2026 with a total of 34 participants. The training methods used included interactive lectures (mini lectures), focus group discussions (FGDs), simulations and direct practice (hands-on practice), empathetic communication roleplays, educational video screenings and reflections. Evaluation of this training was carried out through pre-test and post-test instruments. The results of this training showed a significant increase in participant understanding, from an average score (mean) of 52% in the pre-test to 88% in the post-test. The results of the paired T-test statistical test showed a significant difference between the pre-test and post-test results of the training participants (p < 0.05). The conclusion based on these results is that this care training is effective in increasing the capacity of family caregiver s in optimizing care for the elderly with degenerative diseases. For more optimal results, longer-term training and mentoring by caregiver s is required.